Upaya Meningkatkan Hasil Belajar Akidah Akhlak Melalui Metode Sosiodrama Pada Siswa Kelas VIII MTs Tarbiyah Waladiyah Pulau Banyak - Asmah Apriani, Muhizar Muchtar, Ahmad Zaki (Khazanah : Journal of Islamic Studies, 2023)
This study aims to determine the application of the Sosiodrama Method in Akidah Akhlak subject in class VIII MTs Tarbiyah Waladiyah Pulau Banyak, and to find out whether the application of the Sosiodrama Method can improve student learning outcomes in class VIII MTs Tarbiyah Waladiyah Pulau Banyak. The study is included in action research (action research). The subject of class viii action research is the VIII class MTs Tarbiyah Waladiyah Pulau Banyak with 34 students. The instruments in this study are observation sheets and tests that fit the research procedures by observing cycles I and cycles II. The application of sociodramatic methods can be well accomplished by two cycles. This can be known through the activities that students perform on cycles I and cycles II are increasing. The results of student activity observation in the original learning cycle on the I cycle only reached section 74.76% and then increased by 28.59% to 84.91% of cycle II. There are differences in student studies in the VIII MTS Tarbiyah Waladiyah Pulau Banyak of many before and after the study has been carried out, class action research based on the proficiency of studying in the VIII MTS Tarbiyah Waladiyah Pulau Banyak of lot of pre-cycle 56.32% after using sociodramatic learning methods students' learning increased this can be seen from tests that precycle students' learning ability reached only an average of 56.32 (less) and And increasing in cycle I to 74.76 (sufficient) and in cycle II again to 84.91 (good). The increase in student studies can also increase the percentage of students' acuity on the precycle 56.32% while the I cycle reaches 74.76% and the II cycle is 84.91%.